2009
DOI: 10.1037/a0017469
|View full text |Cite
|
Sign up to set email alerts
|

Betrayal and revictimization: Preliminary findings.

Abstract: The link between childhood sexual abuse and subsequent sexual, emotional, and physical revictimization has been widely reported. The literature is limited, however, in its exploration of the extent to which the level of betrayal inherent in a given childhood traumatic experience affects the likelihood of experiencing similar revictimization in adolescence and adulthood. This study assessed revictimization within a betrayal trauma framework among a sample of 271 college students. As predicted, individuals who r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
79
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 34 publications
8
79
0
1
Order By: Relevance
“…For example, it might be possible to identify particular periods when developing beliefs about trust are most vulnerable to damage by HBT. Previous research (e.g., Gobin & Freyd, 2009) has suggested that individuals who experience HBT during adolescence have the highest risk for future victimization, thus, adolescence may be an optimal period of development during which to intervene on impaired trust and betrayal awareness. Such methods may also enhance our understanding of how deficits in trust create risk for revictimization, in addition to informing intervention methods.…”
Section: Study Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it might be possible to identify particular periods when developing beliefs about trust are most vulnerable to damage by HBT. Previous research (e.g., Gobin & Freyd, 2009) has suggested that individuals who experience HBT during adolescence have the highest risk for future victimization, thus, adolescence may be an optimal period of development during which to intervene on impaired trust and betrayal awareness. Such methods may also enhance our understanding of how deficits in trust create risk for revictimization, in addition to informing intervention methods.…”
Section: Study Limitations and Future Directionsmentioning
confidence: 99%
“…The child's ability to detect the trustworthiness of others may be impaired due to betrayal blindness, thus increasing risk of revictimization (Gobin & Freyd, 2009). In addition to disrupting the ability to make wise decisions about the trustworthiness of others, betrayed children may end up with a general bias such that they are either overly trusting adults or, alternatively, they are unwilling to trust others, even those they should.…”
mentioning
confidence: 99%
“…The most salient example is betrayal blindness, the phenomenon of conscious unawareness that occurs when a trusted or depended-upon other perpetrates abuse (Freyd, 1994(Freyd, , 1997. Such blindness can range from minor (as in the willingness to ignore signs a partner is unfaithful) to extreme (such as total memory absence for instances of physical or sexual abuse; Gobin & Freyd, 2009). It may seem counterintuitive that one would create psychic mechanisms to ignore a source of danger, but individuals are often unable to (or perceive themselves to be unable to) leave the abusive situation (e.g., a child, or a partner with children and no income source).…”
Section: Introductionmentioning
confidence: 99%
“…Substantial empirical support exists for BTT, suggesting that betrayal is a fundamental aspect of psychological trauma (e.g., Kelley, Weathers, Mason, & Pruneau, 2012). For instance, exposure to betrayal trauma has been associated with elevated posttraumatic stress disorder symptom severity (Kelley et al, 2012); impaired cheater detector abilities (DePrince, 2005); physical health symptoms (Freyd, Klest, & Allard, 2005); depression, anxiety, panic, anger, and poor health functioning (Edwards, Freyd, Dube, Anda, & Felitti, 2012); suicidality (Edwards et al, 2012;Gómez & Freyd, 2013); hallucinations (Gómez & Freyd, 2016;Gómez, Kaehler, & Freyd, 2014); elevated rates of revictimization (DePrince, 2005;Gobin & Freyd, 2009); and intergenerational trauma (Hulette, Kaehler, & Freyd, 2011).…”
Section: Bttmentioning
confidence: 99%